Factors Related To Screening Of Cervic Carcinoma With Method IVA At Borongrappoa Health Center Bulukumba Regency - Haerani; Nurul Hidayah Bohari; Kurniati Akhfar; Husnul Khatimah (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2022)
Cervical cancer screening is one way of examining cells for the identification of malignant cells in the cervix at an early stage, by taking cervical cells through a cotton swab and then examining them carefully under a microscope to see the changes that occur. occurs in cells. The research method is quantitative research with a cross sectional study approach. The sampling technique used was purposive sampling. The sample consisted of 118 case groups and 118 control groups. The results showed that marital status had a relationship with Cervical Carcinoma Screening with the IVA Method at the Borongrappoa Health Center, Bulukumba Regency in 2018 with a p_value of 0.00 less than 0.05, meaning there was a relationship. Knowledge has a relationship with Cervical Carcinoma Screening With the IVA Method at the Borongrappoa Health Center, Bulukumba Regency in 2018 with a p_value of 0.00 less than 0.05, meaning there is a relationship. Motivation has a relationship with Cervical Carcinoma Screening With the IVA Method at the Borongrappoa Health Center, Bulukumba Regency in 2018 with a p_value of 0.00 less than 0.05, meaning there is a relationship. To the Borongrappoa Health Center, they pay more attention to WUS who have been married more than once because they are included in the risk group. WUS whose level of knowledge is still low so that screening participation increases by means of health promotion about cervical cancer.